Combined Fit of Spectrum and Composition for FR0 Radio-galaxy-emitted Ultra–high energy Cosmic Rays with Resulting Secondary Photons and Neutrinos - Jon Paul Lundquist; Serguei Vorobiov; Lukas Merten; Anita Reimer; Margot Boughelilba; Paolo Da Vela; Fabrizio Tavecchio; Giacomo Bonnoli; Chiara Righi (The Astrophysical Journal)
This study comprehensively investigates the gamma-ray dim population of Fanaroff–Riley Type 0 (FR0) radio galaxies as potentially significant sources of ultra–high energy cosmic rays (UHECRs, E > 10 ^18 eV) detected on Earth. While individual FR0 luminosities are relatively low compared to the more powerful Fanaroff–Riley Type 1 and Type 2 galaxies, FR0s are substantially more prevalent in the local universe, outnumbering the more energetic galaxies by a factor of ∼5 within a redshift of z ≤ 0.05. Employing CRPropa3 simulations, we estimate the mass composition and energy spectra of UHECRs originating from FR0 galaxies for energies above 10 ^18.6 eV. This estimation fits data from the Pierre Auger Observatory (Auger) using three extensive air shower models; both constant and energy-dependent observed elemental fractions are considered. The simulation integrates an approximately isotropic distribution of FR0 galaxies, extrapolated from observed characteristics, with UHECR propagation in the intergalactic medium, incorporating various plausible configurations of extragalactic magnetic fields, both random and structured. We then compare the resulting emission spectral indices, rigidity cutoffs, and elemental fractions with recent Auger results. In total, 25 combined energy-spectrum and mass-composition fits are considered. Beyond the cosmic-ray fluxes emitted by FR0 galaxies, this study predicts the secondary photon and neutrino fluxes from UHECR interactions with intergalactic cosmic photon backgrounds. The multimessenger approach, encompassing observational data and theoretical models, helps elucidate the contribution of low-luminosity FR0 radio galaxies to the total cosmic-ray energy density.